Prevalence of Noncompliance of Control Visits in HypertensivePatients Treated at Primary Referral Hospitals and Related Factors - Darnindro, Nikko; Sarwono, Johannes (Jurnal Penyakit Dalam Indonesia, 2017)
Introduction. According to WHO, hypertension is associated with 7.5 million deaths worldwide or 12.8% of all deaths. Meanwhile, based on Riskesdas 2013 in Indonesia, hypertension is still a major health problem with a prevalence of 26.5%. Noncompliance is a major cause of treatment failure of hypertension and risk factors for cardiovascular comorbidity. No previous research has been found that examines patient control compliance in the suburban community. This study aims to analyze the prevalence of patients who did not control after hypertension treatment in primary referral hospitals Methods. This study was a retrospective study, by tracking medical records in patients treated between October and December 2015. Results. A total of 80 hypertensive patients participated in the study (55 were females). The mean age was 57.5 ± 11 years, and 22,5% had diabetes mellitus. Mean systolic pressure was 161± 19 mmHg, diastolic pressure was 96 ± 10 mmHg. The majority of the patients had 2nd degree hypertension according to ESC 2013. Sixty percent of patient was given monotherapy and the most frequently prescribed drugs were calcium channel blockers (CCB) (70.0%). The prevalence of loss-to-follow up patient was 63,8% (51/80). Respondents with mono-therapy, without comorbidities, and admission from emergency department were more often loss-to-follow up than those with combination therapy (OR 10.3; 95%CI 3.5 – 30.1), with comorbidities (OR 4,3; 95%CI 1.6 – 11.4), and admission from outpatient clinic (OR 14.6; 95%CI 4.8 – 44.6) although the comorbidities variable was not significant in multivariate analysis. Conclusion. The prevalence of noncompliance of control is still high. Further research is needed to determine other etiological factors.